2019
DOI: 10.4067/s0718-221x2019005000111
|View full text |Cite
|
Sign up to set email alerts
|

Effect of adhesive quantity on selected physico-mechanical properties of Bamboo glulam

Abstract: This study was aimed at determining the optimal glue quantity for bamboo lamination. Bamboo laminated boards were produced using glue applied at three different rates: 150 g/m 2 , 200 g/m 2 and 250 g/m 2. The boards produced were evaluated for their physical (density, longitudinal, tangential, radial and volumetric shrinkage) and mechanical (impact bending strength, modulus of elasticity, modulus of rupture and maximum compressive strength parallel to grain properties. It was discovered that the boards were un… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 8 publications
1
6
0
Order By: Relevance
“…The result of this study is similar to the findings reported by Ogunsanwo et al [38]. For conventional wood, the tangential direction has been accepted as where the greatest dimensional shrinkage occurs whilst the longitudinal shrinkage has been largely reported as the least ranging from 0.1 -0.3% [28,39].…”
Section: Fig 4 Shrinkage Of Glue-laminated Bamboo; N=10supporting
confidence: 89%
“…The result of this study is similar to the findings reported by Ogunsanwo et al [38]. For conventional wood, the tangential direction has been accepted as where the greatest dimensional shrinkage occurs whilst the longitudinal shrinkage has been largely reported as the least ranging from 0.1 -0.3% [28,39].…”
Section: Fig 4 Shrinkage Of Glue-laminated Bamboo; N=10supporting
confidence: 89%
“…The CS of vertically glued laminated bamboo beam from G. pseudoarundinacea, glued with isocyanate adhesive, was 646.8 kg cm -2 (Sulastiningsih et al 2016a), while those bamboo composite lumber from G. pseudoarundinacea, in combination with wood as core layer, had CS values varying from 364.6 to 644.7 kg cm -2 (Sulastiningsih et al 2018). Another previous study carried out by Correal and Lopez (2008) reported that (Oey 1999), based on CS value, the GLBL made of D. asper had strength values comparable to wood strength class I (> 650 kg cm -2 ), while GLBL made of D. giganteus, D. latiflorus and G. levis had strength values comparable to wood strength class II (425-650 kg cm -2 ).…”
Section: Mechanical Propertiesmentioning
confidence: 85%
“…Compared to Indonesian wood strength class (Oey 1999), based on MOR value, the GLBL from D. asper bamboo strips had comparable strength to wood strength class I (> 1100 kg cm -2 ), and those GLBL from D. giganteus and G. levis, to wood strength class II, while the GLBL from D. latiflorus, to wood strength class III. The possible reason which contributed to the higher strength of GLBL made of D. asper is the higher lignin content (32.35%) compared to others bamboo species (24-24.76%) (Damayanti et al 2019).…”
Section: Mechanical Propertiesmentioning
confidence: 86%
“…Bamboo, as a natural and sustainable green material, due to its advantages of rapid growth, abundant resources, and excellent mechanical performance, has been considered as a sustainable alternative to traditional materials such as wood and steel. [ 1–4 ] And many bamboo‐based composites such as bamboo plywood, [ 5 ] bamboo laminated lumber, [ 6,7 ] bamboo scrimber, [ 8,9 ] and so forth were developed and widely used in interior decoration, flooring, furniture, outdoor construction, and other fields. However, currently most of bamboo‐based composites are inseparable from the bonding effect of adhesives, and effective interface bonding strength is the key to ensuring the excellent performance of these composite materials.…”
Section: Introductionmentioning
confidence: 99%